2016
DOI: 10.1074/jbc.m115.712216
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase A (PKA) Type I Interacts with P-Rex1, a Rac Guanine Nucleotide Exchange Factor

Abstract: Morphology of migrating cells is regulated by Rho GTPases and fine-tuned by protein interactions and phosphorylation.PKA affects cell migration potentially through spatiotemporal interactions with regulators of Rho GTPases. Here we show that the endogenous regulatory (R) subunit of type I PKA interacts with P-Rex1, a Rac guanine nucleotide exchange factor that integrates chemotactic signals. Type I PKA holoenzyme interacts with P-Rex1 PDZ domains via the CNB B domain of RI␣, which when expressed by itself faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
51
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 64 publications
(87 reference statements)
8
51
1
Order By: Relevance
“…It is known that PREX1 is phosphorylated in the cell, demonstrated by the fact that after gel electrophoresis, it is detected as multiple bands that are collapsed by both -phosphatase and protein phosphatase 1␣ (PP1␣) (30,31). -Phosphatase and PP1␣ dephosphorylation of PREX1 increase GEF activity, which is consistent with reports showing that PKA phosphorylation of PREX1 leads to a reduction in its in vitro GEF activity both in vitro and in cells (31,32,49). Importantly, PREX1 is phosphorylated after the activation of specific RTKs and GPCRs, indicating that the regulation of PREX1 by phosphorylation has a role in these signaling pathways.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…It is known that PREX1 is phosphorylated in the cell, demonstrated by the fact that after gel electrophoresis, it is detected as multiple bands that are collapsed by both -phosphatase and protein phosphatase 1␣ (PP1␣) (30,31). -Phosphatase and PP1␣ dephosphorylation of PREX1 increase GEF activity, which is consistent with reports showing that PKA phosphorylation of PREX1 leads to a reduction in its in vitro GEF activity both in vitro and in cells (31,32,49). Importantly, PREX1 is phosphorylated after the activation of specific RTKs and GPCRs, indicating that the regulation of PREX1 by phosphorylation has a role in these signaling pathways.…”
supporting
confidence: 78%
“…It is known that PREX1 can be phosphorylated downstream of isoproterenol and sphingosine 1-phosphate (31,49), and in this study we identified additional phosphorylation events on PREX1 after treatment with another GPCR agonist, PGE2. PGE2 is produced through the processing of the fatty acid arachidonic acid and has wide-ranging and diverse roles in physiology in addition to being implicated in cancer (42).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although P-REX1 GEF activity is known to be inhibited by PKAcatalyzed phosphorylation (2), Adame-García et al now report (1) that PKA-RI␣ interacts directly with P-REX1 to increase its GEF activity, an effect that is independent of PKA catalytic subunit activity. This surprising finding is an outgrowth of the same laboratory's prior study, which used a yeast 2-hybrid screen to demonstrate that a fragment of P-REX1 containing two PDZ domains (P-REX1-PDZ1-PDZ2) acted as "bait" to capture its "prey," which corresponded to a C-terminal fragment of PKA-RI␣ (3). At that time, the P-REX1 interaction site on PKA-RI␣ was established to be cyclic nucleotide-binding domain B (CNBD-B), and this site recognized the P-REX1-PDZ1-PDZ2 domains ( Fig.…”
mentioning
confidence: 81%
“…P-Rex1 PDZ domains are also implicated in the interaction between P-Rex1 and ephrin-B1, a transmembrane ligand for the Eph receptor tyrosine kinases involved in neuronal development, as P-Rex1 mutant lacking PDZ domains could not be coimmunoprecipitated with ephrin-B1 in mouse embryonic cortex lysates [44]. Of note, the P-Rex1 PDZ domains also interact with protein kinase A (PKA) [42,45]. PKA potently inhibits P-Rex1 RacGEF activity by phosphorylating the P-Rex1 DEP1 domain and promoting an autoinhibitory conformation, in which the DEP domain and the C-terminal tail obstruct the DH domain catalytic activity [45].…”
Section: Introductionmentioning
confidence: 99%